PENGARUH BUDAYA ORGANISASI DAN DUKUNGAN ORGANISASI TERHADAP KINERJA KARYAWAN DENGAN KNOWLEDGE MANAGEMENT SEBAGAI VARIABEL INTERVENING DI PT.TELEKOMUNIKASI INDONESIA WITEL SURABAYA - Ilmaniar, Haqqi; Djastuti, Indi (Faculty of Economics and Business Diponegoro University, 2018)
The purpose of this study is to analyze the effect of organizational culture, organizational support, on the employee performance with knowledge management as the intervening variable on PT Telekomunikasi Indonesia Witel Surabaya employee.The populations on this study are permanent employees of PT Telekomunikasi Indonesia Witel Surabaya using purposive sampling as a sample collecting technique with the number of participant involved in this studies as much as 100 employees. This study is using Path Analysis as analysis tool with Sobel Test used as tools to test the effects of mediation and using IBM SPSS 23 as data processing program.The result of this study indicates that organizational culture has positive significant effect on knowledge management and also has positive significant on employee performance. Organizational support has positive significant effect on knowledge management but has less significant effect on employee performance. In addition, knowledge management was proven capable as a mediating relationship between organizational culture, organizational support on employee performance